Pendidikan Iman Anak dalam Perkawinan Ekumene di Paroki Katedral Santa Maria Palangka Raya - Yusefina Yusi Nuris; Fransiskus Janu Hamu; Timotius Tote Jelahu (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2019)
This study aims to understand, describe and analyze children faith education in families who marry in different churches. The focus of his research is the implementation of children faith education that has been carried out by parents of different Churches so far. Identifying the efforts of parents of different Churches, both Catholics and non-Catholics, in overcoming the faith education of their children. explain the form of children faith education given by parents of different Churches. Describe the implications of this study for an ecumenically married couple. In this study the method used is a qualitative method Data collection techniques carried out by observation, interviews and documentation. Data analysis techniques using interactive patterns with stages performed 1) gathering information from field data, 2) selecting information based on categories, 3) compiling information in the form of qualitative text and presented in a narrative text, 4) drawing conclusions. The study was conducted at the Cathedral Parish of Santa Maria Palangka Raya Parish. Informants interviewed numbered 8 people consisting of 5 parents who married in different churches and 3 children from couples who married in different churches.